Neurologic Characteristics in Coronavirus Disease 2019 (COVID-19): A Systematic Review and Meta-Analysis - Pinzon, Rizaldy Taslim; Wijaya, Vincent Ongko; Buana, Ranbebasa Bijak; Al Jody, Abraham; Nunsio, Patrick Nalla (Frontiers in Neurology, 2020)
Importance Coronavirus disease 2019 (COVID-19) is a newly emerging infectious disease with a global pandemic. The presenting symptoms are mainly respiratory symptom, yet studies have reported nervous system involvement in the disease. A systematic review and meta-analysis of these studies are required to understanding the neurologic characteristic of the disease and help physicians for early diagnosis and management Objective To conduct a systematic review and meta-analysis on the neurologic characteristics in patients with COVID-19. Evidence Review Authors conducted a literature search through PubMed from January 1st, 2020 to April 8th, 2020. Furthermore, the authors added additional sources by reviewing related references. Studies presenting the neurologic features of COVID-19 patients in their data were included. Case reports and case series also included in this review. The quality of the studies was assessed based on the Oxford Centre for Evidence-Based Medicine guidelines. Selected studies were included in the meta-analysis of proportion and heterogeneity test. Finding From 280 identified studies, 33 were eligible, with 7559 participants included. Most of the included studies were from China (29[88%]). Muscle injury or myalgia was the most common (19.2%, 95%CI 15.4 – 23.2%) neurologic symptoms of COVID-19, followed by headache (10.9%, 95%CI 8.62 – 13.51%); dizziness (8.7%, 95%CI 5.02 – 13.43%); nausea with or without vomiting (4.6%, 95%CI 3.17 – 6.27%); concurrent cerebrovascular disease (4.4%, 95%CI 1.92 – 7.91%); and impaired consciousness (3.8%, 95%CI 0.16 – 12.04%). Underlying cerebrovascular disease was found in 8.5% (95%CI 4.5 – 13.5%) of the studies. Conclusion Neurologic findings are various from nonspecific to specific symptoms in COVID-19 patients. Some severe symptoms or diseases can present in the later stage of the disease. Physicians should be aware of the presence of neurologic signs and symptoms as a chief complaint of COVID-19, in order to improve management and prevent worsening outcome of the patients.